Risk Factors for Adenomyosis - Shrestha, A (Journal of Nepal Health Research Council, 2013)
Background: Adenomyosis was largely underdiagnosed before hysterectomy as little was understood regarding the aetiopathogenesis, clinical symptoms and difficult to confirm pre-operatively. Thus, the aim was to evaluate the possible associated risk factors foradenomyosis Methods: This cross sectional study was done on women who underwent hysterectomy between15th March 2010 to 15th Jan 2012 in Chitwan Medical College. Information was collected on clinical symptoms, menstrual, reproductive factors, contraception history and smoking habits. Presence of adenomyosis was as certained from pathological record. Results: Out of 160 women, adenomyosis was identified in 69 (43.1%).The frequency of adenomyosis was higher in parous women in comparison with nullipara (OR 1.8, 95%CI 1.5-2.0, p